EMF Analysis for a 380kV Transmission OHL in the Vicinity of Buried Pipelines - Mohamed H. Shwehdi; Mohammed A. Alaqil; S. Raja Mohamed (IEEE Access, 2020)
The induction of Electromagnetic Fields that are generated through the interaction of highvoltage transmission lines with neighboring buried metallic pipelines produce uncontrolled hazardous potential voltages, which can infringe safety limits. The paper presents the findings of the electromagnetic interference effects on water buried pipelines constructed within the vicinity of an Extra High-Voltage 380 kV transmission overhead line (OHL) in Riyadh-Salboukh route within the Saudi national grid power network. The presented case study showed that some segments of the buried pipelines under this line have not experienced voltages that exceeded the standard limits for the steady-state condition. However, in the event of L-G fault currents (short circuits), the pipelines experienced a voltage level that is above the local electric utility safety limits. Therefore, the work produced implemented the mitigation method of gradient control wires to reduce the potential voltages experienced by the pipelines to enforce the safety limit. The variation of wire resistance has been proven to be a feasible solution to reduce the excessive induced voltages. The comparison has shown that a 0.1 Ω is sufficient to maintain the safe limit for at least this line. These findings may vary depending on the OHL design and site topology.